Schools days impact on traffic flow in and around school area: case study of Sekolah Kebangsaan Gombak Utara - Hamdan, Hafizuddin; Bachok, Syahriah; Mohamed Osman, Mariana (IIUM Press, 2015)
the study is to assess the impact of school location on the traffic flow during peak hours around the school area in Gombak.